srpski - Donev, Dejan; Vojinović, Maja (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Formulating and respecting professional codes of ethics regarding the duties of journalists, which they should adhere to in the practice of journalism, as a kind of "model" of ethical attitudes, and teaching them how to act in accordance with moral values ​​and norms of their profession, is what saves, rehabilitates and then promotes one profession. Ethical principles are far more than a necessity! The code of ethical journalism must no longer be seen as a "dead letter on paper", a "mere document", but as an opportunity to set and accept certain moral norms that over time should be incorporated into one's professional conduct. This makes the profession easier to perform, and makes life easier because it motivates concrete and active action in that area, as well as an objective judgment about such action. In general, without a high moral structure of journalism, it is illusory to expect good functioning and development of democracy in one society!
Keywords: code of ethics, norm, journalism, professionalism